Myelin Breakdown in Human Huntington's Disease: Multi-Modal Evidence from Diffusion MRI and Quantitative Magnetization Transfer. (1st April 2019) - Bourbon-Teles, José; Bells, Sonya; Jones, Derek K.; Coulthard, Elizabeth; Rosser, Anne; Metzler-Baddeley, Claudia
Highlights: The macromolecular proton fraction (MMPF), an MRI marker of myelin, was reduced in Huntington's disease (HD). MMPF reductions in white matter suggest myelin breakdown. HD was associated with reductions in basal ganglia volume. HD was associated with poor executive functioning but preserved working memory capacity. Axial and radial diffusivities as unspecific metrics of white matter changes correlated with clinical markers of disease. Abstract: Huntington's disease (HD) leads to white matter (WM) degeneration that may be due to an early breakdown in axon myelination but in vivo imaging correlates of demyelination remain relatively unexplored in HD compared to other neurodegenerative diseases. This study investigated HD-related effects on a putative marker of myelin, the macromolecular proton fraction (MMPF) from quantitative magnetization transfer and on fractional anisotropy, axial and radial diffusivity from diffusion tensor MR-imaging. Microstructural differences were studied in WM pathways of the basal ganglia and motor systems known to be impaired in HD: the corpus callosum, the cortico-spinal tract, the anterior thalamic radiation, fibers between prefrontal cortex and caudate and between supplementary motor area and putamen. Principal component analysis was employed for dimensionality reduction. Patients showed reductions in a component with high loadings on MMPF in all WM pathways and a trend for increases in a component loading on axial and radial diffusivities but no differences in a component loading on fractional anisotropy. While patients' performance in executive functioning was impaired, their working memory span was preserved. Inter-individual differences in the diffusivity component correlated with patients' performance in clinical measures of the United Huntington Disease Rating Scale. In summary, HD-related reductions in MMPF suggest that myelin breakdown contributes to WM impairment in human HD and emphasize the potential of quantitative MRI metrics to inform about disease pathogenesis. Disease severity in manifest HD, however, was best captured by non-specific diffusivity metrics sensitive to multiple disease and age-related changes.